1999
DOI: 10.1116/1.591066
|View full text |Cite
|
Sign up to set email alerts
|

Surface-adsorbed polystyrene spheres as a template for nanosized metal particle formation: Optical properties of nanosized Au particle

Abstract: Fabrication of cone-shaped subwavelength structures by utilizing a confined convective self-assembly technique and inductively coupled-plasma reactive-ion etchingThe use of surface-adsorbed monodisperse polystyrene spheres as a template for forming nanosized particles is described. This simple, yet general method is applicable to virtually any material that can be evaporated or sputtered, and monodisperse particles in the size range from tens of nanometers up to tens of micrometers are readily formed. We will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 16 publications
0
53
0
Order By: Relevance
“…The strategy to achieve stronger interaction is based on the concept of templated ordered arrays of nanostructures that can be traced back to the seventies of the last century. [ 63 , 64 ] A typical implementation of this "host-guest" approach is the preparation of Au-capped spheres by evaporation of a metal on MLs of polystyrene spheres [ 65 ] ( Figure 9 ). Since this synthetic work has been ignited by needs in sensing, the choice was made in favor of small size spheres ranging from 50 to 200 nm.…”
Section: Resonant Coupling Of Surface Plasmon Polaritons To Bloch Modmentioning
confidence: 99%
“…The strategy to achieve stronger interaction is based on the concept of templated ordered arrays of nanostructures that can be traced back to the seventies of the last century. [ 63 , 64 ] A typical implementation of this "host-guest" approach is the preparation of Au-capped spheres by evaporation of a metal on MLs of polystyrene spheres [ 65 ] ( Figure 9 ). Since this synthetic work has been ignited by needs in sensing, the choice was made in favor of small size spheres ranging from 50 to 200 nm.…”
Section: Resonant Coupling Of Surface Plasmon Polaritons To Bloch Modmentioning
confidence: 99%
“…[18][19][20][21][22] In principle, MFON is prepared with close-packed nanospheres, but metal particles can also be formed atop a monolayer of randomly adsorbed nanospheres. 23 Some of the features associated with random MFON are (1) spheres do not have to be highly monodisperse, (2) it is possible to mix nanospheres with different diameters to modulate extinction spectra, (3) nanosphere adsorption density can be controlled to modulate the interaction among particles, and (4) a random nanosphere monolayer can be formed over surfaces other than a perfectly flat surface, important in industrial applications. We have explored potentials of random MFON in connection with localized surface plasmon resonance (LSPR) sensing, surface-enhanced fluorescence detection, 28,29 enhanced colorimetric detection, 30 and surface-enhanced Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…We have prepared Au, Ag and Cu with apparent optical density exceeding two, with resonant peaks having FWHM of approximately 100 nm in the reflection mode. 23,24 The peak wavelength can be tuned over the entire visible region as well as into the near infrared region by selection of the nanosphere diameter in the range from tens of nm to hundreds of nm and metal deposition thickness from 5 nm to tens of nm. Baia et al has also shown such dependence on the deposition thickness with close-packed MFON.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of precious metal nanoparticle shapes such as shells [1,2], semi-shells [3], rods [4], caps [5,6], cups [7,8], rings [9,10], rattles [11], triangles [12] and disks [13] have been synthesized. Potential applications of these particles include fields as disparate as medical treatment [14], functional glass windows [15,16] and the sensing of analytes [17].…”
Section: Introductionmentioning
confidence: 99%